Strengthening Policy Capacity for Smart City Emergency Response: Insights from the Cirebon Siaga 112 Program - Zulkarnaen, Iskandar; Suwarsono, Hendri; Heryanto, Yanto; Bharoto, Raden Mahendra Haryo; Sutarjo, Moh (Universitas Teuku Umar, 2025)
The concept of smart city focuses on the use of information and communication technology to improve the efficiency of public services and the quality of life of citizens. In Cirebon City, the implementation of smart city is reflected in the Cirebon Siaga 112 program, which aims to provide fast and effective emergency response services. This study analyzes the policy capacity of the Cirebon Siaga 112 program by assessing analytical, operational and political aspects. The research method uses qualitative with data collection techniques in the form of interviews, observations and documentation studies. The results show that although the use of technology has increased efficiency in emergency response, there are challenges related to system integration, response speed, and personal data protection. Recommendations include continuous improvement in coordination between agencies, officer training, and increased socialization to the community. These findings are expected to help optimize various emergency policies and services in Cirebon City, in accordance with the principles of a smart city.